OPTIMALISASI UNIT PELAKSANAAN TEKNIS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK DALAM PENCEGAHAN KEKERASAN PADA ANAK DI PEKANBARU - Helmi, Kiki; Rahmadan, Davit; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Child protection is all activities to ensure and protect children and theirrights so that they can live, grow, develop, and participate optimally inaccordance with the dignity of humanity, and receive protection from violenceand discrimination. Violence against children in Indonesia from time to timecontinues to occur, even though children are the successors and assets owned bythe nation who will maintain, and realize the ideals of the nation. Women'sempowerment and child protection are critical aspects in efforts to preventviolence against children in Pekanbaru.This type of research is sociological legal research (social legal research),Data obtained by literature review techniques and interviews. This researchfocuses more on the role of the implementation unit for women's empowerment &child protection (UPT PPA) in Pekanbaru City in increasing protection andassistance to children from acts of violence.The results of the study concluded that, first, Efforts made in increasingthe role of the implementation unit for women's empowerment & child protection(UPT PPA) in overcoming criminal acts of violence against children inPekanbaru City are, conducting socialization and education related to theprevention of violence against children and domestic violence, as well as trainingfor domestic violence task force representatives in urban villages in Pekanbarucity, Coordinating with local governments related to a very minimal budget fiberCoordinating with institutions related to the needs of clients or victims of childabuse. Second, the obstacles or constraints faced by the implementation unit ofwomen's empowerment & child protection (UPT PPA) in Pekanbaru City inovercoming criminal acts of violence against children are, (1) lack of budget inproviding assistance to victims of child abuse (2) victims or families who do notreport (3) when children who are victims of violence cannot provide informationbecause they have been affected by their psychological state, (4) lack of facilitiesand infrastructure and (5) lack of professional human resources.Keywords: Children, Violence, Women's Empowerment and Child Protection.